E-Commerce Dispute Resolution Through Online Dispute Resolution - Dg. Takenang, Jusman; Akib, Ma'ruf; Sudirman, Sudirman; Umar, Wahyudi; Alfurqon, Fe Fikran (SASI, 2025)
Introduction: The rapid growth of the e-commerce industry has brought significant economic benefits. Still, it also raises challenges regarding dispute resolution that is efficient, fair and meets the needs of all parties.Purposes of the Research: This study aims to examine and analyze the use of Dispute Resolution in E-commerce (Electronic Commerce) through the Online Dispute Resolution (ODR) mechanism as a solution to provide easier and faster access to justice in the context of online business transactions.Methods of the Research This study uses doctrinal legal research with a statute and conceptual approach. It uses primary legal materials that are authoritative and binding, such as laws and regulations, and secondary legal materials. This study uses legal interpretation techniques as analysis techniques.Results of the Research: The results of this study are expected to provide deeper insight into the potential of ODR in handling e-commerce disputes and its impact on access to justice for all parties involved. This research can also provide recommendations to the government, the e-commerce industry, and other relevant institutions to consider and develop a better framework for integrating ODR in e-commerce dispute resolution to ensure fairness and satisfaction of online businesses.